Propuesta para la organización, gestión y control de inventarios en el establecimiento de comercio Surtiamortiguadores (2023)
This research proposes a proposal for the organization, management and inventory control in the commercial establishment SURTIAMORTIGUADORES, located at 33 Street No. 31-87 in the Porvenir neighborhood, in the city of Villavicencio, department of Meta. It is based on the need to provide an improvement plan and with its implementation contribute with the management and control of the inventory in the storage warehouse of the microenterprise; since, not having the proper organization, management and control of inventories generates affectation in the activities of supply, sales, customers, human talent and physical space